The role of the ruling elites, the religious groups and the women of Calasiao, Pangasinan during the Japanese occupation a case study - Andaya, Russell Gemeniano (1997)
This research tries to look at the role of Calasiao, Pangasinan during the Japanese Occupation. Covert Resistance is the framework of the researcher on talks about non-confrontational activities or resistance done by the three groups. This resistance does not pertain to armed struggle but talks about unarmed struggles such as non-cooperation and disobedience -- Author's abstract.